Lifestyle, metabolite, and genetic determinants of formate concentrations in a cross-sectional study in young, healthy adults. Issue 3 (16th March 2018) - Brosnan, John T; Mills, James L; Ueland, Per M; Shane, Barry; Fan, Ruzong; Chiu, Chi-Yang; Pangilinan, Faith; Brody, Lawrence C; Brosnan, Margaret E; Pongnopparat, Theerawat; Molloy, Anne M
ABSTRACT: Background: Formate is an important metabolite that serves as a donor of one-carbon groups to the intracellular tetrahydrofolate pool. However, little is known of its circulating concentrations or of their determinants. Objective: This study aimed to define formate concentrations and their determinants in a healthy young population. Design: Serum formate was measured in 1701 participants from the Trinity Student Study. The participants were men and women, aged 18 to 28 y, enrolled at Trinity College, Dublin. Formate concentrations were compared with other one-carbon metabolites, vitamin status, potential formate precursors, genetic polymorphisms, and lifestyle factors. Results: Serum formate concentrations ranged from 8.7 to 96.5 µM, with a mean of 25.9 µM. Formate concentrations were significantly higher in women than in men; oral contraceptive use did not further affect them. There was no effect of smoking or of alcohol ingestion, but the TT genotype of the methylenetetrahydrofolate reductase ( MTHFR ) 677C→T (rs1801133) polymorphism was associated with a significantly decreased formate concentration. Formate was positively associated with potential metabolic precursors (serine, methionine, tryptophan, choline) but not with glycine. Formate concentrations were positively related to serum folate and negatively related to serum vitamin B-12. Conclusions: Formate concentrations were sensitive to the concentrations of metabolic precursors. In view of the increased susceptibility of women with the TT genotype of MTHFR to give birth to infants with neural tube defects as well as the effectiveness of formate supplementation in decreasing the incidence of folate-resistant neural tube defects in susceptible mice, it will be important to understand how this genotype decreases the serum formate concentration. This trial was registered at www.clinicaltrials.gov as NCT03305900.